Resistance and Resignation: Responses to Typecasting in British Acting. (September 2017) - Friedman, Sam; O'Brien, Dave
This article draws on 38 in-depth interviews with British actors to explore the operation of typecasting. First, we argue that typecasting acts as the key mechanism through which the 'somatic norm' is established in British acting. It delivers an oversupply of leading roles for white, male, middle-class actors while ensuring that those who deviate somatically are restricted to largely socially caricatured roles. Second, we focus on the career trajectories of 'othered' actors. While they frequently experience acting roles as offensive and discriminatory, we demonstrate how most nonetheless reluctantly accept the terms of their 'type' in order to survive and succeed. Third, we focus on the minority who have attempted to challenge their type. Here we find that successful resistance is accomplished by carefully choosing work that subverts the somatic norm. However, the ability to exercise such choice is highly contingent on resources associated with an actor's class origin.